2013
DOI: 10.1111/1541-4337.12041
|View full text |Cite
|
Sign up to set email alerts
|

Sinapic Acid and Its Derivatives: Natural Sources and Bioactivity

Abstract: Sinapic acid is widespread in the plant kingdom (fruits, vegetables, cereal grains, oilseed crops, and some spices and medicinal plants) and as such is common in the human diet. Derivatives of sinapic acid are characteristic compounds in the Brassicaceae family. Sinapic acid shows antioxidant, antimicrobial, anti-inflammatory, anticancer, and anti-anxiety activity. 4-Vinylsyringol (a decarboxylation product of sinapic acid) is a potent antioxidative and antimutagenic agent which suppresses carcinogenesis and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
231
3
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 412 publications
(244 citation statements)
references
References 179 publications
9
231
3
1
Order By: Relevance
“…The stability and bioavailability of rapeseed phenolics is an issue in terms of the biorefining process and total utilisation of the rapeseed crop (Nićiforović and Abramovič, 2014;Dias et al, 2015). Phenolic compounds are susceptible to spontaneous oxidation and degradation (Tan et al, 2011).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The stability and bioavailability of rapeseed phenolics is an issue in terms of the biorefining process and total utilisation of the rapeseed crop (Nićiforović and Abramovič, 2014;Dias et al, 2015). Phenolic compounds are susceptible to spontaneous oxidation and degradation (Tan et al, 2011).…”
Section: Resultsmentioning
confidence: 99%
“…Bioavailability is a key issue, given that little is known about the metabolism of SA and PCA. The epithelium of the small intestine plays a role in the bioavailability and metabolism of SA, involving both phase I and phase II metabolic enzymes; however, compared to other hydroxycinnamic acids such as ferulic acid, little is known about the metabolism of SA (Nićiforović and Abramovič, 2014). A recent bioavailability study with rats fed the herb Polygonum capitatum found that PCA was primarily distributed in the kidney tissue, followed by the lung tissue; however, >80% was excreted (Ma et al, 2016).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…It has been traditionally cultivated for vegetable oil and animal feed 10,11 . Camelina seed contains potential secondary metabolites namely, phytoalexin as camalexin 12 ; phenols as sinapine (sinapic acid) and phytic acid 13 ; antioxidants as tocopherols 11 , flavonols as quercetin 14 ; omega-3 fatty acids 15 and glucosinolates 16 . The seeds, leaves and roots extracts of camelina contained several anti-insect compounds as natural pesticides that showed strong antimicrobial activity towards a variety of pathogens 17 .…”
Section: Introductionmentioning
confidence: 99%